On the effectiveness of ABH-based metamaterials in vibration control of naval equipment subjected to underwater explosion loads - Jacopo Bardiani; Giada Kyaw Oo D’Amore; Giovanni Marchesi; Marco Biot; Claudio Sbarufatti; Andrea Manes (Results in Engineering)
The dynamic response of marine structures to underwater explosions (UNDEX) is crucial for ensuring onboard equipment’s operational safety and reliability. Non-contact UNDEX events generate shock waves and bubble oscillations that induce vibrations propagating through the hull, potentially affecting sensitive systems. This study proposes a novel numerical framework integrating a high-fidelity acoustic-structural coupled model (CASA) with an Acoustic Black Hole (ABH)-based metamaterial solution to enhance vibration mitigation. A validated finite element model of a full-scale patrol vessel is used to assess the frequency response of equipment mounted on traditional resilient supports. The innovation lies in the integration of ABH into the mounting system, forming a passive control solution tailored to reduce UNDEX-induced excitations. Comparative analyses between conventional mountings and the proposed configuration show that the ABH-based metamaterial effectively attenuates vibrations above its theoretical cut-on frequency, leading to reductions up to 20 m/s² in acceleration amplitude and an average peak attenuation of approximately 61 %. This work represents the first application of ABH technology in a naval context for mitigating UNDEX effects, offering a promising strategy for improving onboard equipment protection.